INTERACTIVE EDUCATIONAL TECHNOLOGIES AS A TOOL FOR FORMING THE GAME-TECHNICAL COMPETENCE OF THE TEACHER: A SYNERGY APPROACH - A. Sukiasyan (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the possibility of using a synergistic approach to creating a system of advanced training for teachers. Digitalization of the educational space, virtual and augmented reality tools used in the educational process are changing the system of requirements for the qualifications of a teacher. Studies on the integration of classical and innovative educational technologies and the synergy of interaction between educational technologies of different types have identified a new problem associated with the game-technical competencies of a modern teacher. The need of the modern Russian school for a teacher of high culture, capable of maintaining a high level ofprofessionalism in a rapidly changing environment is obvious. The evolution of pedagogical science from empirical teaching / education tools to the creation of fundamental principles for the formation of a teacher as a person and a professional is of interest to researchers and practicing teachers. The relevance of the formation of new competencies in the teacher that meet the challenges of society is due to the need of society in the education system, which will ensure the reproduction, development, increase of the intellectual and labor resources of the state. The methodology and possibilities of a synergetic approach to the creation of a system for improving the professional competencies of a